Development Of A Statistical-Analytical Approach For Assessing Coal Bump Potential - Hamid Maleki; Eric Zahl; John Dunford (The National Institute for Occupational Safety and Health (NIOSH))
Coal bumps are defined as sudden failures of rock and coal near entries that are of such a magnitude that they expel large amounts of material into a mine opening. Coal bumps are influenced by geologic conditions, the geometric design of coal mine excavations, and the sequence and rate of extraction. Researchers from private industry and the National Institute for Occupational Safety and Health have studied mechanisms of violent failure and have identified individual factors that contribute to coal bumps. In an attempt to develop tools for assessing coal bump potential, the authors initiated a comprehensive study using information from 25 case studies undertaken in U.S. mines. Multiple linear regression and numerical modeling analyses were used to identify the most significant variables contributing to coal bumps (excluding bumps related to fault-slip). Twenty-five geological, geometrical, and geomechanical variables were considered initially. The most important of these variables were then identified as (1) energy as calculated using the mechanical properties of the strata, depth of overburden, and joint density, (2) mining method, (3) pillar factor of safety, and (4) stress gradient and yield characteristics.